(untitled) (Fiep Bulletin - online, 2011)
The expansion of Capoeira starts in the 1970s and this process was not and is not so easy like it is thought. The comparative study between the practice of Capoeira in Brazil (Curitiba) and in Spain (Autonomous Community of Castilla and León) shows how the introduction and the adaptation of Capoeira in Spain are working through the way of its disseminators are trying to captivate the new followers, understand what are they looking for in this activity and at the same time, to be careful to do not lose its essence. Also, it reveals which kind of people attend to this activity and what is the meaning that they are attributing to its practice nowadays in its original country and in Spain. In order to do this study, 150 Brazilian and Spanish students were interviewed as well 13 Brazilian professionals of Capoeira that were teaching this art in Spain in 2008. As a part of the results, we can notice that while the Brazilian students live Capoeira in all its aspects, the connection between the Spanish students and the Capoeira seems to be only like consumer-product, showing clearly the capitalist society ideals.